The Effectiveness of The National Institutes of Health Stroke Scale (NIHSS) in Determining Nursing Diagnoses in Stroke Patients: A Scoping Review. - Fitriana, Erlis Eka; Haryanto, Haryanto (Journal of Nursing Science Update (JNSU), 2024)
The symptoms of a stroke can vary depending on which part of the brain is affected, potentially leading to severe consequences or difficulties. This scoping review aims to assess the effectiveness of the NIHSS in establishing nursing diagnoses in stroke patients. The review involved searches on Google Scholar, ResearchGate, and PubMed from 2012 to January 2023. The identification and selection of literature followed Moher's guidelines in the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) 2009, resulting in ten articles for discussion. The study utilized the National Institutes of Health Stroke Scale (NIHSS) criteria to evaluate the severity of strokes by assessing neurological impairments. The analysis followed Arksey and O'Malley's model.  The study findings highlighted a significant relationship between NIHSS scores and nursing diagnoses, showing a positive trend where higher NIHSS scores were associated with increased nursing diagnoses. In conclusion, integrating the NIHSS with complementary assessment instruments is crucial in refining nursing diagnoses among stroke patients and enhancing the standard of care and patient prognosis.